PPM Kelurahan Teratai Kecamatan Muara Bulian dalam upaya pemanfaatan lahan pekarangan untuk peningkatan produksi dan kualitas tanaman jahe merah - Nerty Soverda; Zulkifli Alamsyah; Elly Indraswari; Yulia Alia; Neliyati Neliyati (Riau Journal of Empowerment, 2018)
One of the efforts to make efficient use of yard is by planting with plants that are used to meet the needs of themselves and the needs of others. In addition, to make efficient use of land and yard will be well maintained, beautiful and also increase household income. In Teratai village, Muara Bulian sub-district, there is agroindustry based on farmer group which has the healthy drink with the red ginger raw material. They produce these healthy drinks by using raw materials ordered from other regions. This makes agroindustry highly dependent on the supply of others to meet the needs of these raw materials. In this devotional activity carried out demonstration area on the farmyard yard where the Team Dedication as a companion. Through demonstration the farmers' area gets direct guidance from the Community Services Team, seeing and practicing every material given in accordance with the stages of plant development. In this way, it is expected to transfer knowledge and technology effectively from universities to the community. Thus, it is expected to increase the knowledge and skills of farmers in the cultivation of red ginger plants as yard plants, especially ginger farmers in the village of Teratai and generally red ginger farmers in Muara Jambi Regency.